Realizing the Embedded Growth of Large Li(2)O(2) Aggregations by Matching Different Metal Oxides for High‐Capacity and High‐Rate Lithium Oxygen Batteries - Zhang, Peng (Adv Sci (Weinh), 2017)
Large Li(2)O(2) aggregations can produce high‐capacity of lithium oxygen (Li‐O(2)) batteries, but the larger ones usually lead to less‐efficient contact between Li(2)O(2) and electrode materials. Herein, a hierarchical cathode architecture based on different discharge characteristics of α‐MnO(2) and Co(3)O(4) is constructed, which can enable the embedded growth of large Li(2)O(2) aggregations to solve this problem. Through experimental observations and first‐principle calculations, it is found that α‐MnO(2) nanorod tends to form uniform Li(2)O(2) particles due to its preferential Li(+) adsorption and similar LiO(2) adsorption energies of different crystal faces, whereas Co(3)O(4) nanosheet tends to simultaneously generate Li(2)O(2) film and Li(2)O(2) nanosheets due to its preferential O(2) adsorption and different LiO(2) adsorption energies of varied crystal faces. Thus, the composite cathode architecture in which Co(3)O(4) nanosheets are grown on α‐MnO(2) nanorods can exhibit extraordinary synergetic effects, i.e., α‐MnO(2) nanorods provide the initial nucleation sites for Li(2)O(2) deposition while Co(3)O(4) nanosheets provide dissolved LiO(2) to promote the subsequent growth of Li(2)O(2). Consequently, the composite cathode achieves the embedded growth of large Li(2)O(2) aggregations and thus exhibits significantly improved specific capacity, rate capability, and cyclic stability compared with the single metal oxide electrode.